Розуміння сутності та змісту принципу змагальності цивільного процесу за судовою реформою 1864 року та Цивільним процесуальним кодексом УРСР 1924 року - Нестерцова-Собакарь, Олександра Володимирівна; Нестерцова-Собакарь, О. В.; Nestertsova-Sobakar, Oleksandra; Нестерцова-Собакарь, Александра (ВД "Гельветика", 2020)
У статті здійснено ще один крок до поглиблення знань про зміст та особливості реформи цивільного судочинства 1864 року. Особливу увагу приділено Статуту цивільного судочинства та його впливу на розвиток вітчизняного процесуального законодавства як в імперський, так і радянський періоди. З’ясовано сутність та зміст процесуального принципу змагальності через призму судової реформи 1864 року та положення Цивільного процесуального кодексу УРСР 1924 року.

The article takes another step to deepening the knowledge of the content and features of the civil justice reform of 1864. Particular attention was paid to the Statute of Civil Procedure and its influence on the development of domestic procedural legislation in both the imperial and Soviet periods. It is proved that the adoption of the Statute of Civil Procedure in 1864 is largely based on the latest achievements of foreign procedural law and was a significant milestone in the way of creating a qualitative, fast and efficient civil process based on the principles of competitiveness, transparency, veracity, equality of parties, free evaluation and appeal and cassation opportunities. The essence and content of the procedural principle of competition through the lens of judicial reform in 1864 and the provisions of the Civil Procedure Code of the Ukrainian SSR in 1924 have been clarified. The importance of the principle of competitiveness of the civil process, which is manifested in different historical periods of the development of civil procedural legislation, was a complex and multifaceted phenomenon, covering the whole civil process and defining its system. In particular, the principle of competitiveness was given special importance in the organization of civil proceedings and was supported by all known procedural scientists at that time. Adoption of the Statute of Civil Procedure in 1864 for the first time allowed to consolidate the relevant procedural law, but at the same time gave rise to several contradictions, including the fact that the democratic principles of the civil process, enshrined in the judicial reform, faced with the lack of independence and judicial conditions. . The democratic nature of the civil process, as well as of the entire judicial system based on the reforms of 1864, contradicted the essence of the autocratic form of government, which was not matched by the existence of an independent, separate from the administration of the judiciary. As a result, counter-reforms have restricted a number of progressive principles of judicial reform, including the elimination of the peace court, replacing it with administrative and judicial institutions. It emphasized the fundamental differences between the Civil Procedure Code of the Ukrainian SSR of 1924 and the Statute of Civil Procedure, which on the one hand inherited all that was in the previous “imperial” legislation, and used the experience of judicial reform of 1864 and civil procedural legislation of foreign, mainly European countries but on the other, the totalitarian principles of the Soviet power made it impossible to use the competitiveness of the civil process. Even in the Soviet period, when the principle of competitiveness in the civil process was perceived by scientists only in close connection with the activity of the court in evidence, the activities of the parties to prove the circumstances to which they refer as a basis for their claims or objections, were perceived as a procedural obligation.
Нестерцова-Собакарь, О. В. Розуміння сутності та змісту принципу змагальності цивільного процесу за судовою реформою 1864 року та Цивільним процесуальним кодексом УРСР 1924 року / О. В. Нестерцова-Собакарь / // Часопис цивілістики : наук.-практ. журн. / редкол.: Є. О. Харитонов (голов. ред.), О. І. Харитонова (заст. голов. ред.), К. Г. Некіт (відп. секр.), чл. редкол.: С. В. Ківалов, В. В. Завальнюк [та ін.]. – Одеса : Гельветика, 2020. – Вип. 36. – С. 77-81.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; статут цивільного судочинства; судова реформа; цивільний процес; кодифікація; судоустрій; civil procedure statute; judicial reform; civil process; codification; judiciary